Political Clientalism in the Regional Head Election (RHE) Noken System in Jayawijaya Regency, Papua Province - Dafrin Muksin; Siti Khikmatul Rizqi; Ahmad Rizali Pawane (PERSPEKTIF, 2022)
As with other regional head elections (RHE), the noken system elections also have weaknesses in their implementation. For this reason, this study aims to explore the practice of political clientalism in the noken system elections in Jayawijaya Regency, Papua Province. This study uses a qualitative research method with a case study strategy. Creswell (2013) explains that a case study is a research strategy carried out to investigate an event, program, activity of a group of individuals carefully. The data in this study were sourced from interviews and journals that were relevant to the research objectives. The results of the study indicate that the lack of availability of Human Resources (HR) as organizers at the lower level and the unclear data on the Permanent Voter List (PVL), as well as the socio-cultural conditions of the community are obstacles in the implementation of honest and quality Regional Head Election. This weakness is often exploited by candidates for regional heads, thereby opening up space for clientelism practices that ultimately lead to election fraud. The form of clientelism practice in the noken system elections in Jayawijaya Regency is in the form of giving positions and cash by using a traditional approach strategy. The parties who are implementing clientelism start from the district, district and village success teams with targets at lower level actors including District Heads, Tribal Heads, and Village Heads.